El poder de juzgar: una perspectiva comparada entre el juez Colombiano y el jurado Americano (2017)
"From the beginning of the punitive right, which is nothing more than the right of punishment, it has become evident that thinkers, philosophers, jurists and doctrinaires have tried to solve the dilemma brought by the hermeneutics of ""judging"". This indicates the criticism of an action committed; In relation to one or more persons. In this way it starts to solve in a few words and to know through history the transformation and the interpretation that has arisen from it. And so from the concept of reflection and contrast with the study of comparative law who is the legitimate holder or applicator of the same, determining who or who should act as correctors or indults, which is judged. That is to say, that this article is aimed at clarifying, the legitimacy of the right to judge and whether it should be at the head of one or several persons, since this right is fixed or directed to a person to depart or continue exercising Its social and collective right, within a society that manages criteria of conduct, rules, laws and above all levels of coexistence, becoming then a transcendent decision either permissive or strict. For those who judge will have the faculty to determine if that person in his act failed to respect, abide by, comply with and obey these criteria of behavior and why it is resolved if he should be tried, before his fellow men or before an authority centered in the academy of law"